2000
DOI: 10.1515/hf.2000.083
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Hemicelluloses Solubilized during the Treatments of Maize Stems with Peroxymonosulfuric Acid, Peroxyformic Acid, Peracetic Acid, and Hydrogen Peroxide. Part 2. Spectroscopic and Thermal Characterizations

Abstract: Ten hemicellulosic preparations, obtained by treatments of the water-extracted maize stems with peroxymonosulfuric acid, peroxyformic acid, peracetic acid, and 2 % hydrogen peroxide under the conditions given, respectively, were investigated by gel permeation chromatography and spectroscopic techniques such as Fourier transform infrared and carbon-13 nuclear magnetic resonance. Under an optimum extracting condition (2 % H 2 O 2 , 45°C, 12 h, pH 11.5-12.0), the hemicelluloses obtained represented 63.3-64.7 % of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Table 2 shows the content of neutral sugars (relative%) and uronic acids (% dry sample) in the six hemicellulosic fractions and the corresponding two residues. Where applicable, these values are compared to those reported previously (Sun et al, 2000), although the fractionation protocol was not as extensive as that reported in this paper (extraction only in peracids). Obviously, xylose (26.0-27.9%) and arabinose (18.9-22.9%) from the hemicelluloses, and glucose (25.1-30.4%), chiefly from carbohydrates other than cellulose, were the major sugars in the hemicellulosic fractions H 1B and H 1M isolated by 90% neutral dioxane from the ball-milled barley straw and maize stems, respectively.…”
Section: Yield and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the content of neutral sugars (relative%) and uronic acids (% dry sample) in the six hemicellulosic fractions and the corresponding two residues. Where applicable, these values are compared to those reported previously (Sun et al, 2000), although the fractionation protocol was not as extensive as that reported in this paper (extraction only in peracids). Obviously, xylose (26.0-27.9%) and arabinose (18.9-22.9%) from the hemicelluloses, and glucose (25.1-30.4%), chiefly from carbohydrates other than cellulose, were the major sugars in the hemicellulosic fractions H 1B and H 1M isolated by 90% neutral dioxane from the ball-milled barley straw and maize stems, respectively.…”
Section: Yield and Compositionmentioning
confidence: 99%
“…Previously, we have isolated several fractions of hemicelluloses by alkaline hydrogen peroxide (Sun, Tomkinson, Geng, & Wang, 2000). These extracted polysaccharides have been recently modified under mild conditions as cationic and carboxymethyl hemicelluloses with regard to their adsorption onto sulfate kraft pulp and it was found that cationic hemicelluloses and carboxymethyl derivatives could improve the physical properties of hand sheets, while the cooperation of cationic hemicelluloses and carboxymethyl derivatives could enhance sharply the physical properties of hand sheets (Ren, Liu, Sun, She, & Liu, 2007;Ren, Sun, & Peng, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…29 Methods for measurement of the hemicellulosic molecular weights and determination of chemical composition of phenolic acids and aldehydes liberated from alkaline nitrobenzene oxidation of the lignins associated in hemicellulosic fractions have been described in a previous paper. 30 Klason lignin content in hemicellulosic samples was determined according to Tappi method T 249 cm-85. FT-IR spectra were obtained on an FT-IR spectrophotometer (Nicolet 750) using a KBr disc containing 1% finely ground samples.…”
Section: Fractional Extraction Of Hemicellulosesmentioning
confidence: 99%
“…This objective can be achieved by an oxidizing treatment with hydrogen peroxide in alkaline medium, which is able to cause delignification with a reduced environmental impact, leading to solids with enhanced susceptibility to hydrolysis [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%